No Time for Lullabies: Tracing down Pharmacological Effects & Uses of H1-Antihistamines in Children Younger than 6 Years - Alaa Yehya PhD; Mohammad Numan BSc; Laila Matalqah PhD (SAGE Publishing, 2021)
Objectives . To provide a qualitative and a quantitative analysis of H1-antihistamines pharmacological uses pattern among children (<6 years old) and to evaluate the parental-related awareness. Methods . A cross-sectional study was carried out at 5 retail pharmacies in Jordan over 5 months (October/2019-February/2020). Parents who requested any of H1-antihistmine agent for a child (<6 years) were invited to participate. Results . A total of 516 children, most of them were toddlers (1-3) years, received at least 1 H1-antihistamine. More than half of the cases received H1-antihistamine as self-medication (56.3%). Sedating antihistamine agents were the most frequently used among children (<6 years old) (77.9%) among which Chlorpheniramine maleate was the most commonly used agent (62.9%). About half of the children (47.0%) received H1-antihistamine to induce sleep. Whereas, 21.7% and 12.9% received them to manage flu, and allergic rhinitis (AR), respectively. Around 66.6% of the cases were classified as off-label use. Most of the parents (80.5%) were aware of the sedative adverse effects of H1-antihistamines, whereas a fewer number (31.9%) were aware of their cognitive effects. Finally, more than two thirds of parents (79.7%) were unfamiliar with off-label drug use in children. Conclusion . Despite the availability of less-sedating H1-antihistamines with a wide safety and efficacy record, the use of sedating H1-antihistamines remains popular in children.